Value of transfusion independence in severe aplastic anemia from patients' perspectives - a discrete choice experiment - A. Simon Pickard; Lynn Huynh; Jasmina I. Ivanova; Todor Totev; Sophia Graham; Axel C. Mühlbacher; Anuja Roy; Mei Sheng Duh (SpringerOpen, 2018)
Abstract Background Aplastic anemia is a rare, serious blood disorder due to bone marrow failure to produce blood cells. Transfusions are used to reduce risk of bleeding, infection and relieve anemia symptoms. In severe patients, transfusions may be required more than once/week. It is unclear from the patient perspective the impact that transfusions have on quality of life. This study aimed to elicit patient preferences for attributes associated with severe aplastic anemia (SAA) treatment, including transfusion independence. Methods An online discrete choice experiment (DCE) was conducted among patients with SAA who experienced insufficient response to immunosuppressive therapy and transfusion dependence for ≥3 months in the past 2 years. Recruitment occurred through the Aplastic Anemia and Myelodysplastic Syndromes International Foundation and referrals from clinical sites in the US and France. Respondents chose between hypothetical treatment pairs characterized by a common set of attributes: transfusions frequency, fatigue, risk of infection, and risk of serious bleeding. Conditional logit model with effects coding was used to estimate part-worth utilities for different attribute levels and the relative importance of each attribute. Predicted utility scores for transfusion frequency levels were reported. Results Thirty patients completed the survey. Most were age ≥ 40 years (73.3%), female (70.0%), and from the US (86.7%). 33.3% underwent bone marrow transplant; 36.7% received iron chelation therapy. Patients largely agreed that transfusion independence would result in less burden on time and costs, greater control and quality of life, less fatigue (86.7% noted each) and less scheduling around medical appointments (83.3%). The DCE found highest relative importance for risk of bleeding (0.30), followed by risk of infection (0.28), fatigue (0.23), and frequency of transfusions (0.20). More frequent transfusions resulted in lower utility, particularly when increasing monthly transfusions frequency from 4 (0.57) to 8 (0.35). Conclusions Our study showed that higher utility was associated with fewer transfusions in SAA patients with insufficient response to immunosuppressive therapy. While risk of bleeding, risk of infection, and fatigue were more important for patient treatment preferences, frequency of transfusions was also important.